Effects of levamisole on phagocytic activity of rainbow trout (Oncorhynchus mykiss W.) - Ispir, U.; Yonar, M. E. (Veterinarni A Farmaceuticka Univerzita Brno, 2007)
In this study, activation of phagocytic cells was examined in rainbow trout (Oncorhynchus mykiss, W) exposed to 1, 5 and 10 mu g center dot ml(-1) concentrations of levamisole solution. For this purpose, blood samples were taken from fish on days 1, 7 and 14 of exposure. Potential killing activity was determined by measuring oxidative radical production and phagocytic activity of neutrophils and superoxide anion production of phagocytic cells against Y.ruckeri. The activity of phagocytic cells in fish exposed to each of three concentrations was found higher than that in controls and the differences were statistically significant (p < 0.05, p < 0.01). Although no activation in oxidative radical production, phagocytes and bactericidal killing activity in fish exposed to 5 and 10 mu g center dot ml(-1) concentrations of levamisole solution was deten-nined on day 7, it was observed that all indicators increased on day 14 of exposure. The present results suggest that the application of levarnisole in fish farms could increase non-specific immunity and resistance to infection of fish and offer economics benefits.
Keywords: immersion; immunization; levamisole; phagocytes; superoxide anion and Yersinia ruckeri; oxidative radical production